Malaysian government dentists' experience, willingness and barriers in providing domiciliary care for elderly people - Othman, A.A.; Yusof, Z.Y.M.; Saub, R. (Wiley, 2012)
ObjectiveTo assess Malaysian government dentists' experience, willingness and barriers in providing domiciliary care for elderly people. Material and methodsA descriptive cross-sectional study was conducted using a self-administered postal questionnaire targeting government dentists working in the Ministry of Health in Peninsular Malaysia. ResultsSeven hundred and eleven out of 962 dentists responded with a response rate of 74.0%. Only 36.1% of the dentists had experience in providing domiciliary care for elderly people in the past 2years with mean number of visit per year of 1. Younger dentists below the age of 30 and those with confidence in providing the service were the most willing to undertake domiciliary care for elderly patients (OR=13.5, p<0.05). The 3 most reported barriers were patient's complex medical history (74.1%), patient's poor attitude towards oral health service (67.5%), and dentist's unfavourable working condition (64.4%). ConclusionThe majority of Malaysian government dentists had not been involved in providing domiciliary care for elderly patients. Apart from overcoming the barriers, other recommendations include improving undergraduate dental education, education for elderly people and carers, improving dentist's working condition, and introducing domiciliary financial incentive for dentist.